2014
DOI: 10.1177/0741932514557271
|View full text |Cite
|
Sign up to set email alerts
|

CEC’s Standards for Classifying the Evidence Base of Practices in Special Education

Abstract: The application of scientific research has resulted in tremendous gains in many fields. However, Slavin (2002) noted that educational research has been applied haphazardly in schools. The gap between research and practice is particularly problematic in special education, as learners with disabilities require highly effective instruction to reach their potential. Accordingly, bridging the research-to-practice gap is a prominent theme in contemporary special educational reforms. For example, the No Child Left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
396
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(405 citation statements)
references
References 33 publications
5
396
0
4
Order By: Relevance
“…Regarding methodological considerations, future studies are suggested to synthesize the quality of evidence from both group research and single-case research on teaching functional living skills to persons with ASD. Standards of study quality exist from the Council for Exceptional Children which permit such a synthesis (Cook et al 2014). A similar meta-analysis of the existing group research would be a useful area for an extension and a comparison of findings.…”
Section: Future Researchmentioning
confidence: 99%
“…Regarding methodological considerations, future studies are suggested to synthesize the quality of evidence from both group research and single-case research on teaching functional living skills to persons with ASD. Standards of study quality exist from the Council for Exceptional Children which permit such a synthesis (Cook et al 2014). A similar meta-analysis of the existing group research would be a useful area for an extension and a comparison of findings.…”
Section: Future Researchmentioning
confidence: 99%
“…However, individual experimental studies, no matter how carefully designed and conducted, are not sufficient for identifying evidence-based practices (Shadish, Cook, & Campbell, 2002). Another central tenet of scientific research is replication, ensuring that positive findings from an individual study are reproducible and not merely the result of error, bias, or chance (Cook et al, 2015;Makel & Plucker, 2014b). It is only when results from experimental studies are replicated, and more than once, that a practice can truly be considered evidence based (What Works Clearinghouse, 2014).…”
mentioning
confidence: 98%
“…Experimental research has been emphasized in policy documents (e.g., National Research Council, 2002), the priorities of Congress (107th Congress; Education Sciences Reform Act of 2002), and governmental funding agencies (e.g., Institute of Educational Sciences [IES]). In special education, for example, the Council for Exceptional Children has promoted experimental research and developed quality indicators for designing and implementing group and SCD studies as well as standards for classifying evidence-based practices (Cook et al, 2015;Gersten et al, 2005;Horner et al, 2005).…”
mentioning
confidence: 99%
“…Similar to the process used to select children for the Tier 2 study described above, a multiple gating process was used to identify children who would be appropriate candidates for Tier 3 intervention. Measures for universal screening included the Individual Growth and Development Indicators First Sound and Alliteration measures (Wackerle-Hollman et al, 2015 ) and DIBELS Next First Sound Fluency (FSF, Cummings, Kaminski, Good, & O'Neil, 2011 ). In a randomized trial of the intervention across the two states, approximately 30 % of the 106 participants were children with disabilities.…”
Section: Providing Higher Tiers Of Instructional Supportmentioning
confidence: 99%